Microbiology : - Black, Jacquelyn G. (John Wiley & Sons, Inc, 2005)
This photo of Escherichia coli being attacked by bacteriophages highlights rapidly developing technologies for using phages to treat antibiotic resistant infections without destroying normal resident bacteria, and without side effects. Phages are also being used to detect and remove pathogens from our food supplies, both plant and animal. Also exciting is the use of phages as vehicles to delivery DNA vaccines, often directly to mammalian immune system cells. Recent work also suggests possible antitumor effects of phages. We stand on the edge of a whole new world of exploration and applications of microbiology.